2018
DOI: 10.17352/oja.000009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asthma and Its Association with Daily Habits in Jimma Town, Ethiopia

Abstract: Background: Many studies showed a low risk of asthma in sub-Saharan countries. However, due to indoor pollutions and environmental hazards, developing countries are always the prior victims of all types of respiratory illnesses including asthma. Jimma, southwestern Ethiopia, is known by its wide range of vegetations including khat and coffee. Together with high plantation of those cash crops, there is widespread consumption of them by the locals. Objective: To investigate prevalence and severity of bronchial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Bronchial asthma is one of the most common public health problems in Ethiopia. Its prevalence increased over the last few decades with different contributing factors such cigarette smoking [8, 9], household economic status [10], occupational condition of the patients [9], residence of the patients [11], presence of vermin at household [9] and family history of asthma [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bronchial asthma is one of the most common public health problems in Ethiopia. Its prevalence increased over the last few decades with different contributing factors such cigarette smoking [8, 9], household economic status [10], occupational condition of the patients [9], residence of the patients [11], presence of vermin at household [9] and family history of asthma [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite limited documented research on the determinants of asthma, prevalence studies found varying prevalence rates. A systematic review of major NCDs epidemiology ( Misganaw et al, 2014 ) as well as recent prevalence, and associated factor studies in Debrebirhan and Jimma town reported 29.6% and 4.9% rates, respectively ( Tefereedgn & Ayana, 2018 ; Shine, Muhamud & Demelash, 2019 ).…”
Section: Introductionmentioning
confidence: 99%